2015
DOI: 10.1186/s12864-015-1635-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a putative quantitative trait nucleotide in guanylate binding protein 5 for host response to PRRS virus infection

Abstract: BackgroundPreviously, we identified a major quantitative trait locus (QTL) for host response to Porcine Respiratory and Reproductive Syndrome virus (PRRSV) infection in high linkage disequilibrium (LD) with SNP rs80800372 on Sus scrofa chromosome 4 (SSC4).ResultsWithin this QTL, guanylate binding protein 5 (GBP5) was differentially expressed (DE) (p < 0.05) in blood from AA versus AB rs80800372 genotyped pigs at 7,11, and 14 days post PRRSV infection. All variants within the GBP5 transcript in LD with rs808003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 34 publications
5
80
0
4
Order By: Relevance
“…In this study, we aimed to identify genes and mechanisms that affect the susceptibility to PRRSV infection through the integration of eQTL and GWAS analyses. Our results lend further support to the important role of GBP5 in host response to PRRSV infection and also identified additional candidate genes within the top GWAS regions associated with VL and WG reported in earlier studies456.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…In this study, we aimed to identify genes and mechanisms that affect the susceptibility to PRRSV infection through the integration of eQTL and GWAS analyses. Our results lend further support to the important role of GBP5 in host response to PRRSV infection and also identified additional candidate genes within the top GWAS regions associated with VL and WG reported in earlier studies456.…”
supporting
confidence: 87%
“…A recent study6 showed that pigs with the susceptible genotype (Allele A of WUR10000125, associated with increased VL) expressed GBP5 at a lower level than the resistant genotype and primarily produced an alternate splice form that was predicted to produce a truncated protein. That study focused on the WUR region and tested differential expression and splicing using the 16 animals from trial PHGC3 and validated the results using the 28 animals from trial PHGC5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excitingly, this effect was confirmed for a second strain of the virus (Hess et al, 2014), suggesting that it could be possible to select for pigs that are less impacted by PRRSV when it is present. Sequencing of blood samples from pigs showing different viremia and growth responses appears to have identified the causative mutation responsible for reduced susceptibility (Koltes et al, 2015). Other regions of the genome that were identified to influence susceptibility had relatively small effects (less than 2.6% of genetic variance for weight gain and less than 1.2% for virus load) .…”
Section: Variation In Susceptibilitymentioning
confidence: 99%